Sources of polarized positrons for colliders - Bulyak, E.V. (Вопросы атомной науки и техники, 2014)
A number of projects of the electron-positron colliders are now under development such as ILC/CLIC, LHeC, TLEP and others. These colliders are intended for investigations the fundamental properties of matter in “post LHC era.” These accelerator facilities imply use of the beams of polarized positrons. Comparative parameters of two major schemes of such sources – based on application of undulators and Compton scattering of laser beams for production of polarized gamma photons – are reported. Degree of polarization are estimated, ways to enhance the efficiency of sources are indicated as well. “Proof-of-principle” experiments are also proposed. В настоящее время разрабатывается несколько проектов электрон-позитронных коллайдеров на высокие энергии, предназначенных для исследований фундаментальных свойств материи в «пост LHC эру», таких как ILC/CLIC, LHeC, TLEP и др. Эти установки предполагают использование поляризованных позитронов. Приведены сравнительные характеристики двух основных способов получения позитронных пучков: ондуляторного и комптоновского. Оценена степень поляризации пучка, а также намечены пути повышения эффективности источников. Рассматриваются возможности экспериментальной проверки эффективности схем формирования позитронных пучков. В цей час розроблюється декілька проектів електрон-позитронних колайдерів на високі енергії, які можуть бути використані для досліджень фундаментальних властивостей матерії в так звану «після LHC еру». Це такі проекти, як ILC/CLIC, LHeC, TLEP та інші. Ці прискорювальні установки будуть використовувати поляризовані позитрони. Наведено порівняльні характеристики двох основних способів отримання таких позитронних пучків: ондуляторного та комптонівського. Дається оцінка ступеня поляризації пучка, а також окреслено шляхи підвищення ефективності джерел. Розглядається можливість експериментальної перевірки ефективності схем формування позитронних пучків.